Relationship between Nutritional Status, Sleep Patterns, and Breast Care with Exclusive Breastfeeding at the Sukajadi Banyuasin Public Health Center in 2021 - Meliyasari Meliyasari; Helni Anggraini; Turiyani Turiyani (Science Midwifery, 2022)
Backkground: Based on data from the Ministry of Health 2020, the coverage of infants receiving exclusive breastfeeding in South Sumatra Province in 2019 was 57.79%. Based on data from the Banyuasin District Health Office in 2019, the coverage of infants receiving exclusive breastfeeding was 56.3%. Based on data from the Sukajadi Banyuasin Health Center in 2020, exclusive breastfeeding for breastfeeding mothers reached 64.6%. Nutritional status, sleep patterns, and breast care are factors that influence exclusive breastfeeding. This study aims to determine the relationship between nutritional status, sleep patterns, and maintenance of sleep patterns with exclusive breastfeeding at the Sukajadi Banyuasin Public Health Center. This research is a type of cross sectional research, namely research to study the correlation between factors by approach, observation or data collection with 30 respondents using accidental sampling technique. The independent variables used were nutritional status, sleep patterns, and breast care, while the dependent variable was exclusive breastfeeding. This study uses univariate and bivariate data analysis techniques. The results of this study obtained that the results of the Chi Square statistical test of nutritional status obtained p value = 0.026 (α < 0.05), the results of the Chi Square statistical test of sleep patterns obtained 0.030 (α < 0.05), the results of the Chi Square statistical test of breast care obtained p value = 0.022(α < 0.05). From the results of this study, it can be concluded that there is a relationship between nutritional status, sleep patterns, and breast care with exclusive breastfeeding at Puskesmas Sukajadi Banyuasin.